Pengaruh Daya Tarik Lokasi, Word of Mouth, Harga Kompetitif terhadap Kinerja Pemasaran - Graciela, Priscillia; Siam, Stivenes Tjin (Jurnal Informatika Ekonomi Bisnis, 2025)
This study aims to determine the effect of location attractiveness, word of mouth, and competitive prices on the marketing performance of Fashion MSMEs in Pontianak City. The problem taken in this study is the phenomenon of increasingly tight competition in the MSME fashion sector, as well as pricing strategies that affect marketing performance. A quantitative approach was used with a causal associative research design. Primary data were collected through questionnaires distributed to 125 business actors selected using a purposive sampling technique. The measuring tool used for data tabulation was the Rating Scale which was then processed and analyzed using SPSS version 25. The results showed that location attractiveness had a positive effect on marketing performance, word of mouth had a positive effect on marketing performance, and competitive prices had a positive effect on marketing performance.